Entrepreneurial Intention among Engineering Students: The Role of Attitude, Personality and Demographics - Paudel, Samundra; Gautam, Dhruba Kumar; Regmi, Indira (Journal of Science and Technology, 2024)
Entrepreneurship intention is an important determinant for increasing the probability of entrepreneurial behavior among youth. The literature review identified eight different determinants - entrepreneurship attitude, subjective norm, perceived behavioral control, desire for success, creativity, attitude towards money, gender, and family background - and examined their impact on the entrepreneurship intentions of undergraduate engineering students. Responses of 245 engineering students were collected through a paper-based questionnaire from four colleges in the Kathmandu Valley. The regression model revealed that entrepreneurship attitude, perceived behavior control, creativity, gender, and family background had a significant impact on the student’s entrepreneurship intention. The results provide valuable insights for researchers, educators, and policymakers to better understand the factors affecting students’ entrepreneurship intentions and design and implement entrepreneurship development activities in HEIs